The surrendered : reflections by a son of Shining path - Agüero, José Carlos (Duke University Press, 2021)
"The Surrendered is Peruvian public intellectual José Carlos Agüero's reflections on his parents--who were executed by the state for being Shining Path militants--as well as the legacies of the Peruvian internal armed conflict and the possibility for forgiveness and reconciliation in the face of hate."--